PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA - Hurint, Paskalis Kristoforus Deka; Prayekti, Prayekti; Subiyanto, Didik (STKIP Persada Khatulistiwa Sintang, 2023)
Human Resources is a determining factor in the success of an organization. Democratic leadership style can influence aspects of organizational life. Work motivation can encourage employees to do their work well. An important factor in improving performance is the work environment, where the creation of an effective work environment can increase job satisfaction within the organization. The purpose of this research is to analyze and determine the influence of democratic leadership style, work environment, and work motivation on job satisfaction at the regional secretariat of East Flores Regency. The research design used in this research uses casual research with a quantitative approach. Primary data in this research is data obtained through the results of questionnaires distributed to employees and measured using a Likert scale. The population in this study were 144 employees working in the East Flores Regency regional secretariat office with a research sample of 59 people taken using the accidental sampling technique. Data is processed and analyzed through validity, reliability, classical assumption tests, and multiple regression analysis. The research results show that there is a positive and significant influence of democratic leadership style and work motivation on work satisfaction. However, work environment variables do not affect job satisfaction.